Individual Differences in Mentalizing Capacity Predict Indirect Request Comprehension. Issue 8 (17th November 2019) - Trott, Sean; Bergen, Benjamin
ABSTRACT: People often speak ambiguously, as in the case of indirect requests . Certain indirect requests are conventional and thus straightforward to interpret, such as "Can you turn on the heater?", but others require substantial additional inference, such as "It's cold in here." How do comprehenders make inferences about a speaker's intentions? And what makes a comprehender more or less successful? Here, we explore the hypothesis that comprehenders do so in part by mentalizing —encoding what the speaker knows or believes about the world—and that differences in mentalizing ability predict how well comprehenders draw these inferences. In Experiment 1, we find that comprehenders' pragmatic interpretations are significantly influenced by a speaker's inferable knowledge states. In Experiment 2, we find that variability in this effect is explained by individual differences in comprehenders' mentalizing ability. Finally, in Experiment 3, we find that both effects are robust across different dependent measures of inference.